O gótico e a brasilidade em Lúcio Cardoso (Revista do Centro de Estudos Portugueses, 2008)
Este trabalho desenvolve o percurso intertextual do Gótico literário anglosaxão  do século XVIII na escrita do romancista mineiro Lúcio Cardoso (1912-  1968), em seus vários desdobramentos, como a tese do feminino enquanto  agente destruidor do patriarcalismo, as marcas do Gótico hollywoodiano, e os  traços do vampirismo literário, em suas diversas manifestações. O desejo  enquanto clausura e o pastiche intratextual convivem na narrativa cardosiana  aqui estudada, que exibe o comparecimento, dialético, tanto da “verdade” da  hermenêutica quanto da “mentira” da teatralização. This work traces the intertextual presence of eighteenth-century Anglo-Saxon  Gothic literature in the writing of Brazilian novelist Lúcio Cardoso (1912-  1968), in its many unfoldings, such as the thesis of the female as the destroyer  of patriarchalism, the trappings of Hollywood Gothic, and the marks of literary  vampirism in its several manifestations. The concept of desire as imprisonment  and the intratextual pastiche go hand in hand in the “cardosian” narrative  here studied, which exhibits the dialectic presence of both the “truth” of  Hermeneutics and the “deception” of theatricality.